Fundamental Analysis on substrate distortion induced by Wire Arc Additive Manufacturing using experiment and nonlinear FEM with simplified bead model - P Prajadhiana, Keval; HP Manurung, Yupiter; Minggu, Zaidi; HS Pengadau, Fetisia; Leng Choo, Hui; Graf, Marcel; Haelsig, Andre; Adams, Tom-Eric; P Ishak, Dendi (International Journal of Engineering and Technology, 2018)
In this fundamental research, Wire Arc Additive Manufacturing (WAAM) was investigated experimentally with regard to process parameter, bead quality and bead model development. A series of experiment was conducted by using robotic welding system ABB IRB 2400/16 and KEMMPI Pro Evolution ProMIG 540MXE  with Æ1.2mm  filler wire (AWS A5.28 : ER80S-Ni1) and shielding gas (80% AR/ 20% CO2) on 6mm-thick substrate of Low Carbon Steel S235. Based on the experimental result, WAAM geometry is modelled using simplified bead shape following rectangular form under consideration of diluted material. The simulation was carried out by utilizing thermo-mechanical Finite Element Method (FEM) under consideration of non-linear isotropic hardening using commercial FEM software MSC Marc/Mentat. The plasticity model of Low carbon steel and high strength steel also considered under material properties option featured in software database. As comparison, similar material properties from previous researches were implemented into simulation to ensure a realistic resemblance. The analysis of substrate distortion is carried out by utilizing the coordinate measurement machine (CMM) pointed on various locations of substrate with 10 layers and 1 string WAAM. Based on the results between experiment and simulation, it is found out that FEM result with simplified bead model and equivalent plasticity model exhibits a good agreement which falls under the acceptable range of error.